2018
DOI: 10.22499/4.0031
|View full text |Cite
|
Sign up to set email alerts
|

Bureau Research Report

Abstract: The Bureau of Meteorology advise that the information contained in this publication comprises general statements based on scientific research. The reader is advised and needs to be aware that such information may be incomplete or unable to be used in any specific situation. No reliance or actions must therefore be made on that information without seeking prior expert professional, scientific and technical advice. To the extent permitted by law and the Bureau of Meteorology (including each of its employees and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…On one hand, it can be observed a differentiation of predominantly active DWTs in consecutive IPO phases, most persistent during the off‐season months (May–October) as well as in transitional months (November–December and March–April). Salinger et al (2001) also showed that the IPO represents a major source of decadal climate variability in the SWP, which is consistent with the findings of Greenslade and Gregory (2023) who showed that before and after 2000 the relationship between TC activity and several climate indices in the SWP changed significantly. On the other hand, at the interannual time scale, ENSO has been proven to modulate climate variability through the equatorial SST gradient and thus influencing TC activity.…”
Section: Time‐scales Variabilitysupporting
confidence: 73%
“…On one hand, it can be observed a differentiation of predominantly active DWTs in consecutive IPO phases, most persistent during the off‐season months (May–October) as well as in transitional months (November–December and March–April). Salinger et al (2001) also showed that the IPO represents a major source of decadal climate variability in the SWP, which is consistent with the findings of Greenslade and Gregory (2023) who showed that before and after 2000 the relationship between TC activity and several climate indices in the SWP changed significantly. On the other hand, at the interannual time scale, ENSO has been proven to modulate climate variability through the equatorial SST gradient and thus influencing TC activity.…”
Section: Time‐scales Variabilitysupporting
confidence: 73%
“…Out of this ensemble, 200 tracks are selected, and these drive a 200‐member storm surge model ensemble. This results in forecasts for a worst‐case scenario (98th percentile surge height) and a most likely surge forecast based on the official forecast track (Greenslade et al., 2017). Similarly, the US National Weather Service uses a probabilistic TC storm surge (P‐Surge) model to assess storm surge risk.…”
Section: Introductionmentioning
confidence: 99%
“…Dullaart et al [40] examined the performance of global surge simulation forced by the climate reanalysis datasets, and showed that the accuracy of storm surge simulation depends on whether the reanalysis data can accurately describe the intensities of tropical cyclones (10 m winds and mean pressure). In order to overcome the problem of underestimating tropical cyclone intensities via reanalysis data, the meteorological forcing derived from parametric tropical cyclone models is often applied to drive storm surge models [41,42], such as a symmetric wind model- Holland (1980) [43]-some asymmetric wind field models (such as the generalized asymmetric Holland model, GAHM [44], the Willoughby model [45] and the Ueno model [46]). In addition, the Hurricane wind (H*wind) [47] and Weather Research and Forecasting for Hurricanes (HWRF) models [48] are also effective when it comes to improving the quality of typhoon wind field and further improving the accuracy of storm surge simulation.…”
Section: Introductionmentioning
confidence: 99%